1998
DOI: 10.1086/514610
|View full text |Cite
|
Sign up to set email alerts
|

Failed Postnatal Immunoprophylaxis for Hepatitis B: Characteristics of Maternal Hepatitis B Virus as Risk Factors

Abstract: A retrospective case-control study was conducted to determine why some infants born full-term without obstetric intervention to hepatitis B e antigen (HBeAg)-seropositive mothers become infected by hepatitis B virus (HBV) despite having received passive-active immunoprophylaxis. Cases and controls comprised 12 hepatitis B surface antigen (HBsAg)-seropositive infants and 22 HBsAg-seronegative infants, respectively. Infants infected by putative vaccine-escape mutants were excluded. Risk factors, after adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 1 publication
3
59
1
3
Order By: Relevance
“…The latter can be exactly reflected through HBV DNA quantitation by FQ-PCR test clinically [8,9] . With the prominent sensitivity and specificity of the FQ-PCR test, our study indicated that the intrauterine infection rate had significant correlation with the level of HBV DNA in the maternal serum before delivery, which showed an ascendant trend; the intrauterine infection rate significantly increased at the level of HBV DNA 10 8 copies/mL, which was consistent with the findings by Ngui et al [10] . Those findings suggest that the threshold of HBV DNA 10 8 copies/mL is a potent index of HBV intrauterine infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The latter can be exactly reflected through HBV DNA quantitation by FQ-PCR test clinically [8,9] . With the prominent sensitivity and specificity of the FQ-PCR test, our study indicated that the intrauterine infection rate had significant correlation with the level of HBV DNA in the maternal serum before delivery, which showed an ascendant trend; the intrauterine infection rate significantly increased at the level of HBV DNA 10 8 copies/mL, which was consistent with the findings by Ngui et al [10] . Those findings suggest that the threshold of HBV DNA 10 8 copies/mL is a potent index of HBV intrauterine infection.…”
Section: Discussionsupporting
confidence: 91%
“…The quantity of HBV DNA was transformed to the form of log 10 and then expressed as mean±SD. All data were analyzed as χ 2 (chi-square) test for positive difference and t test for comparisons of means between the 2 groups using SPSS 10.0 for windows.…”
Section: Statisticsmentioning
confidence: 99%
“…The protection rate for postnatal vaccines in our study was 95%, which is similar to the finding of 93.1% in a previous report (14). However, this rate may fluctuate with maternal HBeAg status.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, infection risk has been related to the presence of DNA in the placenta (61) and to maternal viremia (4,38), supporting an association between the state of maternal HBV during pregnancy and the risk of transmission to the baby. It is unclear whether HBV can traverse intact epithelial barriers to infect the fetus during gestation.…”
mentioning
confidence: 92%